Body composition, strength and specific physical fitness as factors to discriminate performance in judokas - Tavares Junior, Antonio Carlos [UNESP]; Olivio Junior, Jose Alfredo [UNESP]; Goncalves, Beatriz [UNESP]; Drigo, Alexandre Janotta [UNESP]; Dos-Santos, Julio Wilson [UNESP] (Archives Budo Science Martial Arts & Extreme Sports, 2018)
Background & Study Aim: Body composition, maximum strength and the special judo fitness are determining factors to high-level judo performance. The aim of the present study was to relationships between indicators of body composition, maximum strength and special judo fitness can discriminate between judokas of different competitive levels who have yet to reach international status. Material & Methods: A total of 19 judokas, aged 24.3 +/- 5.3 years were divided into two groups, according to the titles or classification won in the previous 3 years in regional (RE) or state and national (SN) competitions. Body composition, the 1-RM test of squat, supine and a barbell row (B-Row), and the Special Judo Fitness Test index (SJFT-I) were applied to both groups. Results: Body fat (BF), fat-free mass (FFM), lean body mass (LBM) and body fat percentage (BFP) were not determining factors to indicate judokas level. However, 1-RM of the squat and B-Row test identified athletes with the best competitive performance. The SN group obtained the best SJFT index (SJFT-I). Conclusions: The 1-RM test with squat and row exercises, as well as the SJFT-I were able to identify judokas with the best competitive performance. Although BF and body composition can vary between weight categories, it is not a good indicator to differentiate regional judokas from their state and national counterparts.
Keywords: 1-RM; combat sports; competitive levels; maximal strength; performance; Special Judo Fitness Test